The Role of Legal Aid Institutions in Providing Legal Aid to Women as Victims of Sexual Violence - Anita Damayanti (Journal of Law Science, 2022)
The purpose of this research is to know the legal aid effort given by LBH APIK to victims of sexual violence and obstacles faced by LBH APIK in providing legal assistance to women victims of sexual violence. This research is a field research, the data collected by the method of interview to the parties related to the research topic. In addition, the authors also conduct literature research through related data and books related to research topics. Furthermore, the data are analyzed qualitatively and presented descriptively. The results showed that: 1) Legal standing of Legal Assistance Association of Indonesian Women Association for Justice as known as LBH APIK in providing legal assistance to women victims of violence is based on Law Number 16 in Year 2011 about Legal Assistance, Law Number 18 in Year 2003 concerning Advocates and Standard Operating Procedures as known as SOP. The role in providing legal assistance to women as victims is litigation and non-litigation. Litigation is a process of assistance from the beginning of handling cases to verdicts in court, non-litigation is a process outside the court that is until the mediation step. In addition, LBH APIK performs other legal reinforcements such as legal counseling and legal seminars conducted in the region of Makassar. 2) The Obstacles faced by LBH APIK in handling the case is the victim who is reluctant to tell his case as well as the police who assume that if there is sexual violence in women it is on the basis of mutual desire factor not because of coercion factor.